Revisitando o velho modelo de decadência em Goiás - Barbosa, Augusthus Luiz de Souza (2017)
Information obtained in the documentation of the Overseas Historical Archive provided the elaboration of the History of Goiás. Reports and offices of the administration of the captaincy of Goiás since the beginning of exploration of the gold found by the bandeirante Bartolomeu Bueno da Silva served as beacon in the composition of historical moments of Goiás, as well as the memorialistic records of European travelers who passed through Goiás in the nineteenth century and their considerations on the eighteenth century. Briefly, according to the historiography on Goiás, the decadence of the Goiás captaincy would have begun with the diminution of the extraction of gold, that reduced the collection of the Real Fifth and other contracts of the administration, like the Tithes and the Entries. Withless gold, the miners could not keep up their operating logistics, resulting in not paying off their debts and getting less and less slaves. Trade, which depended on the demand for gold for business, suffered great losses. The administration without the tax dividends failed to make the necessary investments to develop other areas of production. The miners who did not leave because they were almost bankrupt, still managed to survive for a few years of gold until it was impossible to deal with it and they left for agriculture and livestock. A ruralized population, producing more for subsistence than for export, isolated by poorly maintained roads, continued in this situation because of an inert policy of maintaining power until the victory of the 1930 revolution, with Pedro Ludovico chanting a modern thought against backwardness of the State of Goiás in relation to other States. Because they are supported by documents, these historiographical and memorialistic works have acquired a certain empiricism because they are based on official sources. Without the proper questioning of the official sources, the History of Goiás told by these historians and memorialists had in its course a period of decadence of the captaincy caused by the decay of gold that began in the third quarter of the eighteenth century, that is, from the decade of 1780. Confronted with the historiographic works on Goiás and the sources that helped to form his narrative, with the original documents of the Overseas Historical Archive, technical flaws and precipitated judgments were identified in the identification of the end of the XVIII century as the initial mark of the decadence of the captaincy of Goiás. A necessary revision to relativize the History of Goiás formed of conceptual misunderstandings.